Жужелицы (Coleoptera, Carabidae) заболоченных участков Крыма - Петрусенко, А.А.; Петрусенко, С.В. (Вестник зоологии, 1973)
The data on a species composition of ground beetles and ecological and zoogeographical analyses of Carabidae fauna from the bogged up areas of the Crimea are presented. Biocenotic relations of ground beetles with different invertebrates and vertebrates living here substantiate the peculiarity of the bogged up habitats (plavni, bed kettle, spring fens) as independent units enjoying equal significance with other flood-plain biogeocenoses of the peninsula.